1979
DOI: 10.1111/j.1748-1716.1979.tb06439.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of muscle temperature on maximal muscle strength and power output in human skeletal muscles

Abstract: The influence of muscle temperature (Tm) on maximal muscle strength, power output, jumping, and sprinting performance was evaluated in four male subjects. In one of the subjects the electromyogram (EMG) was recorded from M. vastus lateralis, M. biceps femoris, and M. semitendinosus. Tm ranged from 30.0 degrees C to 39 degrees C. Maximal dynamic strength, power output, jumping, and sprinting performance were positively related to Tm. The changes were in the same order of magnitude for all these parameters (4-6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
234
4
8

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(262 citation statements)
references
References 10 publications
16
234
4
8
Order By: Relevance
“…Karvonen 26 has demonstrated that increased temperature improves central nervous system function and increases the transmission speed of nervous impulses. Single leg vertical jump height was less in Ice pack with Active warm-up protocol than the other warm up protocols which are consistent with the findings of the Bergh and Ekbon because there is a positive relationship between the muscle temperature and the height of vertical jump 29 . Bergh and Ekbonbest demonstrated this relationship finding that the height of the jump decreases with a decrease in muscle temperature at a rate of 4.2% x degree C -129 .Decreases in CMJ height could also be attributed to changes in dynamic strength following the application of cold.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Karvonen 26 has demonstrated that increased temperature improves central nervous system function and increases the transmission speed of nervous impulses. Single leg vertical jump height was less in Ice pack with Active warm-up protocol than the other warm up protocols which are consistent with the findings of the Bergh and Ekbon because there is a positive relationship between the muscle temperature and the height of vertical jump 29 . Bergh and Ekbonbest demonstrated this relationship finding that the height of the jump decreases with a decrease in muscle temperature at a rate of 4.2% x degree C -129 .Decreases in CMJ height could also be attributed to changes in dynamic strength following the application of cold.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it appeared that agility was affected immediately following cold application 32. Speed, a component of agility, has not been studied in great detail. Bergh & Ekblom 29 are the pioneer researchers who attempted to quantify the effects of muscle temperature on speed. They found sprint performance measured on a bicycle ergometer was significantly reduced with a decreased muscle temperature.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that muscle temperature (T m ) has a significant effect on muscle function, force and power production (Asmussen and Boje 1945;Bergh and Ekblom 1979;De Ruiter and De Haan 2000;Edwards et al 1972;Racinais et al 2005;Sargeant 1987). Much of the available literature suggests that events that require high levels of power production tend to benefit from increases in muscle temperature (Asmussen and Boje 1945;Hajoglou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the available literature suggests that events that require high levels of power production tend to benefit from increases in muscle temperature (Asmussen and Boje 1945;Hajoglou et al 2005). For example, it has been reported that there is a ~4% .˚C-1 improvement in vertical jump performance as T m increased (Bergh and Ekblom 1979). In addition, it has been shown that changes in T m following water immersion of the legs influences maximal power output during isokinetic sprint cycling (Sargeant 1987).…”
Section: Introductionmentioning
confidence: 99%
“…power) to a given electrophysiological excitation or descending voluntary drive (Feretti 1992;Oksa et al, 2002). This is widely attributed to reductions in muscle temperature (Bergh & Ekblom 1979a) which reduces contractile function due to slowed intramuscular energetics and peripheral nerve conduction velocities (Kossler et al 1987;Bigland Ritchie et al 1981;Bergh, 1980;Faulkner et al 1990;Sweitzer & Moss 1990;Feretti 1992;De Ruiter & De Haan 2000;Allen et al 2008;Racinais & Oksa, 2010;Cahill et al 2011;Cè et al 2012). Several studies report that action potential propagation, ATP hydrolysis, Ca 2+ handling and sensitively as well as cross-bridge force kinetics are adversely affected by lower tissue 3 temperatures (Kossler et al 1987;Sweitzer & Moss 1990;Mucke & Heuer 1989;Feretti 1992;Oksa et al 2002Cè et al 2012.…”
Section: Introductionmentioning
confidence: 99%